Redundant roles for histone H3 N-terminal lysine residues in subtelomeric gene repression in Saccharomyces cerevisiae. - Martin, Amy M (2004)
The transcription of genes located in subtelomeric regions of yeast chromosomes is repressed relative to the rest of the genome. This repression requires wild-type nucleosome levels but not the telomere silencing factors Sir2, Sir3, Sir4, and Rap1. Subtelomeric heterochromatin is characterized by the absence of acetylation or methylation of histone H3 lysine residues, but it is not known whether histone H3 hypoacetylation or hypomethylation is a prerequisite for the establishment of subtelomeric heterochromatin. We have systematically mutated the N-terminal tails of histone H3 and H4 in Saccharomyces cerevisiae and characterized the effects each mutant has on genome-wide expression. Our results show that subtelomeric transcriptional repression is dependent on the histone H3 N-terminal domain, but not the histone H4 N-terminal domain. Mutating lysine-4, lysine-9, lysine-14, lysine-18, lysine-23, and lysine-27 to glycine in histone H3 is also sufficient to significantly reduce subtelomeric gene repression. Individual histone H3 lysine mutations, however, have little effect on subtelomeric gene repression or genome-wide expression, indicating that these six lysine residues have redundant functions. We propose that acetylation and methylation of histone H3 N-terminal lysine residues act as redundant mechanisms to demarcate regions of euchromatin from heterochromatin.